2006
DOI: 10.15695/vurj.v2i0.2732
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Childhood Stuttering on Attention Regulation in Emotionally Arousing Situations

Abstract: The purpose of this study was to examine the relation between children's attention regulation and stuttering in three different emotionally arousing situations. Participants were 15 monolingual, Standard American English speaking, preschool children who stutter (CWS) and 17 monolingual Standard American English speaking, preschool children who do not stutter (CWNS) between the ages of 3; 0 (years; months) and 5; 7. All participants had speech, language, and hearing development within normal limits, with the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…However, findings based on parent-reports (Anderson et al, 2003; Craig et al, 2003; Eggers et al, 2010; Embrechts et al, 2000; Felsenfeld et al, 2010; Karrass et al, 2006; Vanryckeghem et al, 2001; Wakaba et al, 1998), behavioral observations of young (Bush, 2006; Johnson et al, 2010; Karrass et al, 2006; Schwenk et al, 2007) and older preschool-age children (Eggers et al, 2012) as well as attention regulatory abilities of adults (Bosshardt, 1999, 2006; Bosshardt et al, 2002; Heitmann et al, 2004; Smits Bandstra et al, 2006) contradict this conclusion. It is more than likely the case that the affect manipulation associated with the cueing task, as used in the present study, did not provide a substantial amount of arousal to influence affect-related reaction times.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, findings based on parent-reports (Anderson et al, 2003; Craig et al, 2003; Eggers et al, 2010; Embrechts et al, 2000; Felsenfeld et al, 2010; Karrass et al, 2006; Vanryckeghem et al, 2001; Wakaba et al, 1998), behavioral observations of young (Bush, 2006; Johnson et al, 2010; Karrass et al, 2006; Schwenk et al, 2007) and older preschool-age children (Eggers et al, 2012) as well as attention regulatory abilities of adults (Bosshardt, 1999, 2006; Bosshardt et al, 2002; Heitmann et al, 2004; Smits Bandstra et al, 2006) contradict this conclusion. It is more than likely the case that the affect manipulation associated with the cueing task, as used in the present study, did not provide a substantial amount of arousal to influence affect-related reaction times.…”
Section: Discussionmentioning
confidence: 99%
“…Findings based on parent-report have suggested that CWS, when compared to CWNS, exhibit lower or maladaptive AR (Eggers et al, 2010; Felsenfeld, van Beijsterveldt, & Boomsma, 2010; Karrass et al, 2006) and specific difficulty with maintaining (Embrechts et al, 2000) and shifting attention from one task to another (Anderson et al, 2003). Bush (2006), employing direct observations of preschool-age CWS and CWNS attentional behavior, reported that CWS took significantly longer than CWNS to look away from a focal point (the computer monitor) to begin a narrative task after listening to an audio-taped emotionally arousing conversation. Her finding suggests that CWS are less distracted than CWNS, a finding consistent with Anderson et al (2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When examined on a study-by-study basis, findings indicate that young CWS, when compared to young CWNS, are (a) more reactive to environmental stimuli (Wakaba, 1998), (b) more negative in their affect/emotions (Howell et al, 1987; Johnson, Walden, Conture, & Karrass, 2010; Ntourou, Conture, & Walden, 2011), (c) less able to maintain attention and less adaptive to their environment (Anderson, Pellowski, Conture, & Kelly, 2003; Embrechts, Ebben, Franke, & van de Poel, 2000), (d) less able to disengage their attention when required (Bush, 2006) or shift attention (Heitman, Asbjørnsen, & Helland, 2004; Eggers, De Nil, & Van den Bergh, 2010), (e) more likely to exhibit problematic scores on attention scales based on caregiver report (Felsenfeld, van Beijsterveldt, & Boomsma, 2010), (f) less able to ignore changes in irrelevant background stimuli (Schwenk et al, 2007), (g) significantly less efficienct in orienting of attention (Eggers, De Nil, & Van den Bergh, 2012; cf. Johnson, Conture, & Walden, 2012), and (h) lower in inhibitory control, as well as significantly higher in anger/frustration, approach and motor activation (Eggers, De Nil, & Van den Bergh, 2010).…”
Section: Temperament: Methods Of Measurementmentioning
confidence: 99%
“…Lewis & Goldberg, 1997; Williams, 2006). In contrast, there fewer findings have been based on behavioral observation (for exceptions, see Bush, 2006; Schwenk et al, 2006). Thus, there would appear to be some need for more direct behavioral observations of children’s emotional and related behaviors, particularly in reference to stuttering.…”
mentioning
confidence: 99%